KEPENTINGAN KAZAKHSTAN SEBAGAI MEDIATOR DALAM KRISIS HUBUNGAN TURKI DAN RUSIA TAHUN 2015 - Erfandi Fahmi Rizal; Muhammad Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research explains Kazakhstan interests in mediating the conflict between Russia and Turkey in 2015, which began with the shooting down of a Sukhoi Su-24 by a Turkish F-16 jet that crashed in Syrian territory, and caused conflicts in the Central Asian region, this made Kazakhstan a mediator. conflict. this research uses a Realist perspective by using the concept of national interest from a Realist point of view. The theory used in this research is the theory of conflict resolution according to Levine with the level of analysis of the nation state. This research uses qualitative methods with data collection techniques in the form of written text journals, books, official websites, websites, and media. the result of this study is that Kazakhstan has managed to avoid the negative impact of the Russian-Turkish conflict and maintain its interests in the Central Asian Region by becoming a conflict mediator Keywords : Kazakhstan Interest, Mediator, Russian-Turkish conflict